INNOVATION IN LEARNING: DESIGNING KELADI APPLICATIONS USING C# - Ilmi, Muhammad Bahrul; Simanjuntak, Nadia Costarika; Al Husna, Saiba; Siregar, Hanfiandi Akbar; Syahputra, Fahmy (Institut Teknologi Nasional Malang, 2024)
Technological developments such as the development of digital-based learning media have a major impact on the world of education. This study aims to design and develop the KelaDi (Digital Class) application using Visual Studio and the C# programming language as an interactive learning media for students. The KelaDi application has various features that support the teaching and learning process, such as e-books and e-book readers, learning videos, uploading assignments, and quizzes. The methodology used in this study is a qualitative methodology using the Waterfall model software development approach. The development process includes the stages of requirements analysis, system design, coding and testing program. Supporting software includes Visual Studio 2019 and SQL Server Management Studio 20 software. This program is built using NET 4.7.2 framework technology with the C# programming language. The author hopes that the birth of this program can help support digital-based learning